The joint effect of genetic risk factors and different types of combined oral contraceptives on venous thrombosis risk - Khialani, Deeksha (Br J Haematol, 2020)
It is not known whether the synergistic effect of genetic markers, increasing the risk of venous thrombosis (VT), and combined oral contraceptives (COC) use varies between different types of progestogens in these preparations. We investigated the joint effect of genetic risk factor, that is, F5 rs6025, F2 rs1799963, and FGG rs2066865 mutations, and different progestogens on the risk of VT. The constrained maximum likelihood estimation (CMLE) method was used to calculate joint effects, expressed as odds ratio (OR) with 95% confidence intervals [CI]. As the dose of estrogen is known to be a risk factor for VT, analyses were restricted to COC with 30 µg estrogen and each progestogen. Overall, the joint effect of COC and genetic variants was lowest for COC containing the progestogen levonorgestrel, albeit CIs were wide. The OR (95% CI) of the four different analyses (i.e. joint effect with F5 rs6025, F2 rs1799963, F5 rs6025 or F2 rs1799963 and FGG rs2066865) ranged between 7·4 (5·4–10·2) and 24·8 (12·3–50·0) for levonorgestrel. For gestodene the joint effect ranged between 11·7 (7·2–19·1) and 30·9 (10·6–89·9). Desogestrel and cyproterone acetate had the highest risk estimates: 14·6 (9·7–21·9) and 32·6 (13·2–80·6) and 15·5 (9·7–24·9) and 44·4 (16·9–116·3) respectively. In women with inherited thrombophilia, COC containing levonorgestrel were associated with the lowest risk of VT, albeit the CIs were wide.